A territorialização da variedade Moscato Branco de Farroupilha e a identidade vitivinícola de Farroupilha/RS: novos desafios - Zilio, Tiago Antônio (My University, 2019)
The theme of the dissertation is the organization of space and structuring of the territory of the Farroupilha municipality in Rio Grande do Sul state, with a wine identity linked to the cultivation of the Moscato Branco de Farroupilha grape variety, in the context of the Italian immigration to the Serra Gaucha in the late 19th century, based on small property and family work. The general objective was to analyze the process of territorialization of the Moscato Branco de Farroupilha grape variety, in the Farroupilha municipality, characterizing the identity of viticultural and muscats sparkling wines with the Farroupilha Geographical Indication, as well as their perspectives, presenting actions to strengthen and enhance the culture. The exploratory method was used through interviews and questionnaires with closed and open questions for winegrowers (in print) and adolescent students (online) in the Farroupilha municipality, as well as in documentary sources and the registration process of the Farroupilha Geographical Indication. The information was organized for content analysis, including spreadsheets for the application of basic statistics. The results showed the process of territorialization of the Moscato Branco grape variety, until it became the Moscato Branco de Farroupilha, identifying the main actors responsible for the diffusion of the variety and how, in some decades, its cultivation and product - the grape and the wine - became part of Farroupilha's wine identity and the Farroupilha Geographical Indication region. Regarding the future of viticulture of muscats, the results of the research with adolescents indicated many difficulties for its continuity, but at the same time, they showed great opportunities for actions in the public sector, the grape and wine production sector, and the academic community to reverse the trend. From the results and the correlated analysis of the information, an educational action was proposed for the grape and wine culture, within the municipal education system, for the valorization of the viticultural identity, the Farroupilha Moscato Branco variety and viticulture in general, in the context of the municipality of Farroupilha and the Farroupilha Geographicak Indication region.
O tema da dissertação é a organização do espaço e a estruturação do território do município de Farroupilha, Rio Grande do Sul, com uma identidade vitivinícola relacionada ao cultivo da variedade Moscato Branco de Farroupilha, no contexto da imigração italiana na região da Serra Gaúcha, no final do século XIX, baseada na pequena propriedade e no trabalho familiar. O objetivo geral foi analisar o processo de territorialização da variedade Moscato Branco de Farroupilha, no município de Farroupilha, caracterizando a identidade da vitivinicultura de moscatéis da Indicação de Procedência Farroupilha, bem como suas perspectivas, propondo ações de fortalecimento e de valorização da cultura. Foi usado o método exploratório, por meio de entrevistas e questionários com questões fechadas e abertas para viticultores (em meio impresso) e alunos adolescentes (on-line) no município de Farroupilha, bem como em fontes documentais e do processo de registro da Indicação de Procedência Farroupilha. As informações foram organizadas para análise do conteúdo, inclusive em planilhas para aplicação de estatística básica. Os resultados evidenciaram o processo de territorialização da Moscato Branco em Farroupilha até se tornar a Moscato Branco de Farroupilha, sendo identificados os principais atores responsáveis pela difusão da variedade e como, em algumas décadas, seu cultivo e produto – a uva e o vinho - passou a ser parte da identidade vitivinícola de Farroupilha e da região delimitada da Indicação de Procedência Farroupilha. Em relação ao futuro da vitivinicultura de moscatéis, os resultados da pesquisa com adolescentes indicaram muitas dificuldades para sua continuidade, porém, ao mesmo tempo, evidenciaram grandes oportunidades para ações do setor público, do setor produtivo da uva e do vinho e da comunidade acadêmica, para reverter a tendência. A partir dos resultados e da análise correlacionada das informações, foi proposto uma ação educativa para a cultura da uva e do vinho, no âmbito do sistema de ensino municipal, para a valorização da identidade vitícola e da variedade Moscato Branco de Farroupilha, como também da vitivinicultura geral, no contexto do município de Farroupilha e da região da Indicação de Procedência Farroupilha.
Keywords: Vinho e vinificação - Farroupilha (RS); Uvas - Cultivo; Wine and wine making - Farroupilha (Brazil); Viticulture